A survey on secure communication technologies for smart grid cyber physical system - Giriraj Sharma (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Recent advancements in communication technologies and embedded system design have popularized the practical application of cyber–physical systems (CPS). A CPS combines physical components, computational elements, and communication networks. The smart grid CPS (SG-CPS) is an example of such a system, featuring physical devices with diverse communication needs and intermediary networks. Consequently, robust and secure communication networks are essential for optimal performance of the SG-CPS. This paper provides an overview of current technologies in SG-CPS, its implementation, benefits, and security issues. Our goal is to summarize the latest advancements, provide researchers with a comprehensive list of references, and encourage further exploration into this rapidly growing field.